Immunosuppressive effect of the gut microbiome altered by high‐dose tacrolimus in mice. Issue 7 (3rd February 2018) - Zhang, Z.; Liu, L.; Tang, H.; Jiao, W.; Zeng, S.; Xu, Y.; Zhang, Q.; Sun, Z.; Mukherjee, A.; Zhang, X.; Hu, X.
Abstract : The alterations induced in gut microbiota by tacrolimus may affect immune function and organ transplantation. Mice were treated with high‐dose tacrolimus for 14 days. The fecal microbiota were analyzed by pyrosequencing the 16S rRNA genes, and the effect on metabolism was predicted using the sequence data. The subgroups of T cells in the serum, gut‐associated lymphoid tissue, and draining lymph nodes were determined by flow cytometry. Tacrolimus treatment significantly altered the relative abundance of Allobaculum, Bacteroides, and Lactobacillus and CD4 + CD25 hi FoxP3 + regulatory T cells in the colonic mucosa and the circulation. These were significantly increased after either tacrolimus treatment or treatment by fecal microbiota transfer from tacrolimus‐treated donors. Further, treatment with low‐dose tacrolimus plus fecal microbiota transfer from high‐dose tacrolimus–altered mice increased skin allograft survival rate in a skin transplantation model. Thus, high‐dose tacrolimus alters the compositions and taxa of the gut microbiota. Administration of these conditioned gut microbiota plus low‐dose tacrolimus resulted in regulation of colonic and systemic immune responses and an increased allograft survival rate. This study demonstrated a new strategy for controlling allograft rejection by combining an immunosuppressive agent with gut microbiome transplantation. Abstract : In a mouse model, gut microbiome transplantation plus low‐dose tacrolimus results in the suppression of colonic and systemic immune responses and an increased allograft survival rate.